2D AUTOCAD GEOMETRIC DATA EXTRACTION AND POST- PROCESSING FOR NUMERICAL CONTROL - Mwinuka, Tito E; Mutagahywa, Beda M (Tanzania Journal of Engineering and Technology, 2017)
In this paper, a method of extracting 2D geometric data from AutoCAD drawing and post- processing for Numerical Control (NC) is presented. Geometric data already available in the Drawing Interchange Files (DXF) can be utilized to accurately and economically prepare part programs for controlling NC/CNC machine tools. AutoCAD, being general purpose software, stores its geometric data in a form that cannot be directly applied for automatic generation of Numerical Control (NC) codes. The way around the discrepancy between the structure of a drawing database (DXF files) and the information requirement for part programming is addressed in this work. NC programming of a test component drawn in AutoCAD is also presented.